Integrative genomic analyses reveal an androgen-driven somatic alteration landscape in early-onset prostate cancer - Weischenfeldt, Joachim; Simon, Ronald; Feuerbach, Lars; Schlangen, Karin; Weichenhan, Dieter; Minner, Sarah; Wuttig, Daniela; Warnatz, Hans-Jörg; Stehr, Henning; Rausch, Tobias; Jäger, Natalie; Gu, Lei; et al. (Cancer cell, 2013)
Early-onset prostate cancer (EO-PCA) represents the earliest clinical manifestation of prostate cancer. To compare the genomic alteration landscapes of EO-PCA with “classical” (elderly-onset) PCA, we performed deep sequencing-based genomics analyses in 11 tumors diagnosed at young age, and pursued comparative assessments with seven elderly-onset PCA genomes. Remarkable age-related differences in structural rearrangement (SR) formation became evident, suggesting distinct disease pathomechanisms. Whereas EO-PCAs harbored a prevalence of balanced SRs, with a specific abundance of androgen-regulated ETS gene fusions including TMPRSS2:ERG, elderly-onset PCAs displayed primarily non-androgen-associated SRs. Data from a validation cohort of > 10,000 patients showed age-dependent androgen receptor levels and a prevalence of SRs affecting androgen-regulated genes, further substantiating the activity of a characteristic “androgen-type” pathomechanism in EO-PCA.